Abdominal actinomycosis mimicking acute appendicitis. (26th November 2015) - Conrad, Robert Joseph; Riela, Steven; Patel, Ravi; Misra, Subhasis
Abstract : A 52-year-old Hispanic woman presented to the emergency department, reporting worsening sharp lower right quadrant abdominal pain for 3 days. CT of the abdomen and pelvis showed evidence of inflammation in the peritoneal soft tissues adjacent to an enlarged and thick-walled appendix, an appendicolith, no abscess formation and a slightly thickened caecum consistent with acute appendicitis. During laparoscopic appendectomy, the caecum was noted to be firm, raising suspicion of malignancy. Surgical oncology team was consulted and open laparotomy with right hemicolectomy was performed. Pathology reported that the ileocaecal mass was not a malignancy but was, rather, actinomycosis. The patient was discharged after 10 days of intravenous antibiotics in the hospital, with the diagnosis of abdominal actinomycosis. Although the original clinical and radiological findings in this case were highly suggestive of acute appendicitis, abdominal actinomycosis should be in the differential for right lower quadrant pain as it may be treated non-operatively.